Knitting Force Measurement on Flat Knitting Machines. (5th August 2014) - Fouda, A.; El-Hadidy, A.; El-Deeb, A.
Abstract : Knittability can be defined as the ability of yarns to run on knitting machines without problems. Knittability can be achieved when less stress is applied on the knitting machine parts by the knitting yarns. This paper presents a novel measuring system for the knitting force needed to perform knitting yarns on flat knitting machine based on data acquisition system (DAS). The proposed system is used to measure the knitting force at different machine settings and different properties of the knitting yarns to determine the optimal production conditions. For this reason, three types of knitted fabric structures (single jersey, Rib 1 × 1, and full cardigan) with three different loop lengths and five different twists of ply yarn were produced. The obtained results showed the optimal yarn ply twist factor( α e ) which gave minimum knitting force (less stress on needles or knitting yarns) at different loop lengths for each structure.